Assessing behavior in children aged 12–24 months using the Strengths and Difficulties Questionnaire. (20th July 2021) - Patel, Jinal; Smith, Ria; O'Farrelly, Christine; Iles, Jane; Rosan, Camilla; Ryan, Rachael; Ramchandani, Paul
Abstract: Behavioral and emotional problems in infants and toddlers are common, often persist and put children at risk of later mental health problems. Reliable, efficient, and sensitive tools are needed to identify young children who may benefit from further assessment and support. The Strengths and Difficulties Questionnaire (SDQ), offers a brief, convenient means of screening for early problems, however, it lacks psychometric validation in infants. The aim of this study was to assess the validity and reliability of the SDQ in children aged 12–24 months. Ninety‐three participants, with children aged 12–24 months, completed the SDQ and Child Behavior Checklist (CBCL) online. Concurrent validity of the SDQ was assessed through comparison with the CBCL. The results demonstrated that key subscales of the SDQ and CBCL were significantly correlated ( r range= −.19 to –.57). Key SDQ subscales showed moderate reliability (Cronbach's alpha range = .38–.79, mean inter‐item correlation range = .06–.43). The SDQ shows promising reliability and validity as a measure for rating the behavior of 12–24‐months‐old children, particularly for externalizing symptoms. Further research is needed to assess its predictive utility.